Knowledge Management Systems (KMS) for libraries: The implementation strategy and development issues for management - Ruzaif Adli, Md. Daud; Norehan, Dato’ Ahmad; Wan Abdul Malik, Wan Abdullah (Universiti Sains Malaysia, 2010)
International Conference On Libraries (ICOL) 2007, 31st October - 2nd November 2007 organized by Universiti Sains Malaysia (USM) with the coorperation of Librarians Association of Malaysia at Gurney Hotel, Penang.